The analysis of long-term borehole heat exchanger system exploitation - Jaszczur, Marek; Śliwa, Tomasz (Computer Assisted Methods in Engineering and Science, 2017)
The key issue in designing borehole heat exchangers (BHE) is the long-term performance of the ground source heat pump (GSHP) systems. The performance directly reflects economic profitability and depends on a large number of parameters including rock formation, the construction of the borehole heat exchangers, working parameters (circulation rates) and thermal load. The objective of the paper is to perform a realistic long-term (up to 10 years) analysis of the ground system to show possible degradation of efficiency over time. A mathematical model of the heat transfer in a borehole heat exchanger and the surrounding area has been constructed for parameters of the currently running experimental system. The long-term performance of the ground source heat pump system is evaluated.